Intermarriage, language, and economic assimilation process: a case study of France - Xin Meng; Dominique Meurs (Institute for the Study of Labor (IZA), 2006)
Lack of economic assimilation of immigrants often results in social and political unrest of a society. The increased desire to understand better the nature of the assimilation process of immigrants is due to increased immigration flows in many western countries. In this paper we try to study the role of intermarriage in the process of immigrant economic assimilation in France. We find that among all immigrants those who are intermarried earn around 17 per cent more than those who are endogamously married. Once taking into account individual characteristics and endogeneity of intermarriage, the premium is around 25 to 35 per cent. In addition, the intermarriage premium is substantially higher for individuals who have better grasp of French language before migration than for those whose language skill is poor. This result seems to suggest that, perhaps, immigrants who have a strong base in the native language can better reap the gain from intermarriage.
urn:nbn:de:101:1-20080516188
Keywords: 330